PENGARUH PROFITABILITAS, STRUKTUR KEPEMILIKAN DAN KUALITAS AUDIT TERHADAPMANAJEMEN LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Bahana Takbir Aljana; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
This study aims to determine the effect of profitability, institutional ownership, managerial ownership and audit quality to earnings management The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the year 2013-2015. He sampling technique used is purposive sampling. The analysis tool used is multiple linear regression analysis. Based on the results of tests conducted it can be concluded that: Profitability has a positive and significant impact on earnings management. Instutional ownership has a negative and insignificant effect on earnings management. Managerial ownership has a negative and significant effect on earnings management. The size of KAP has an insignificant positive effect on earnings management.